Analisis Perbedaan Sebelum dan Sesudah Pemberian KUR Mikro dari Bank BRI terhadap Perkembangan Usaha Mikro Kecil di Kabupaten Kendal (Studi Kasus: Kecamatan Kaliwungu, Kecamatan Boja, dan Kecamatan Limbangan) - Erliyan Lutfi Pambudi; Achma Hendra Setiawan (Diponegoro Journal of Economics, 2020)
The limited capital owned by Micro and Small Enterprises in Kendal Regency is an obstacle to business development which in turn will affect the sales and also the profit obtained. With Micro People Business Credit program from BRI Bank, it is expected to have a change in impact for Micro and Small Business actors’ from before obtaining Micro People Business Credit and after obtaining Micro People Business Credit from BRI Bank. Based on these reasons, this study aims to analyze the differences before and after obtaining Micro People Business Credit to the Micro and Small Business in Kendal Regency. This study uses primary data by distributing questionnaires to 95 respondents of Micro and Small Business in Kendal Regency. In order to achieve the research objectives, this study uses a Validity Test, and Reability analysis tool to measure the accuracy of the questionnaires that have been distributed, and the Wilcoxon Signed Rank Test to determine whether there are differences due to the impact of Micro People Business Credit from BRI Bank for Micro and Small Entrepreneurs in Kendal Regency. Validity and reliability test results show that the questionnaire has been distributed to 95 respondents is valid and reliable. The results of the Wilcoxon Signed Rank Test of 95 respondents examined showed that Micro People Business Credit from BRI Bank can help Micro and Small Entrepreneurs to increase capital, the turnover of sales, and profit. The capital increased by 97%, sales turnover increased by 65%, increase in turnover accompanied profit increased by 98% after obtaining Micro People Business Credit from BRI Bank.